Reconstruction of buccal mucosa: A minimalist symbiotic approach with local flaps. (March 2021) - Dhara, Vasantha; Kudva, Adarsh; Chithra, A.; Rajan, Jyotsna; Singh, Anupam
Highlights: Buccal mucosa reconstruction is critical to maintain form and function of the oral cavity. Defects extending posteriorly to the soft palate and tonsillar pillars can be reconstructed with the combination of flaps. The concept of combined local flaps is an viable option avoiding sophisticated free flaps. Abstract: Background: Buccal mucosa defects following resection of premalignant or malignant lesions require adequate reconstruction. Both locoregional and microvascular flaps have been extensively used based on operator and patient factors. This paper focuses on the outcomes of a simplified approach for reconstruction of large buccal mucosa defects with posterior extent using a combination of two loco regional flaps. Method: A combination of buccal fat pad graft and nasolabial flap was used to reconstruct large defects spanning the buccal mucosa extending to the soft palate or retromolar trigone areas. Post operative outcomes were noted in patients who underwent reconstruction using this combination technique. Result: This paper highlights the favourable results and ease of technique with this combination of flaps, i.e complete coverage of large buccal mucosa defects extending to critical areas such as soft palate, retromolar trigone or tonsillar pillars; avoiding sophisticated free flaps. Satisfactory healing with adequate functional and esthetic outcomes were seen. Conclusion: Defects post ablation of buccal mucosa lesions, larger than 5 cm × 5 cm, can be reconstructed using double local flaps. Buccal fat pad and nasolabial flaps heal excellently with nil morbidities and their combination provides a simple and an economical alternative option for reconstructive surgeons.